Rasio Hutang dan Profitabilitas terhadap Valuasi Perusahaan Perbankan Selama Pandemi - Sella Fahima Ariyani; Ana Kadarningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
An investor's evaluation of a company's performance is predicated on its market value. A firm's stock market performance may be discerned through its value. Public perception will indicate that a company's future prospects and performance are favorable in proportion to its valuation. The aim of this study is to ascertain the impact of the Debt to Equity Ratio and Net Profit Margin on the valuation of companies, as well as the extent to which Sales Growth can influence company value. For the period of 2019 to 2022, the population of this study comprised 47 banking sector corporations that were publicly listed on the Indonesia Stock Exchange. Utilizing a variety of predetermined criteria, Purposive sampling technique was used for sample selection. A total of 172 data from 43 companies were sampled for this four year observation period. Descriptive statistical analysis, trials for normality, heteroscedasticity, autocorrelation, multicollinearity, multiple linear regression, coefficient of determination, and F test are all components of the research analysis method. SPSS Statistics 25 is the analytical instrument utilized. As demonstrated by the research findings, the Debt to Equity Ratio and Net Profit Margin are two variables that significantly impact the value of a company. Furthermore, with regard to the value of a company, Sales Growth has no appreciable impact.